Complications of pterygium excision with limbal auto-graft transplantation - Cheleva Markovska V. (Hungarian Ophthalmology society and SEEOS, 2018)
Aim: To evaluate the early and late complications after pterygium excision with limbal auto graft transplantation Material and methods: 40 cases with primary unilateral nasal pterygium were evaluated. Outcomes were evaluated in terms of complication and recurrence after pterygium excision. The patients were divided in two groups: 1. a group of 20 patients with primary pterygium length over the cornea 1.0 mm to 3 mm 2 a group of 20 patients with primary pterygium length over the cornea 3 mm and more. Results: Mean follow up time after the surgery was 15 months (6 to 24 months) Three of forty (7,5%) pterygium recurred after the pterygium excision with limbal auto graft transplantation. All three recurrences (3 cases) were after the excision of pterygium reaches more than 3 mm of the cornea. The most common postoperative complaint was irritation or foreign body sensation, followed by wetting photophobia and blepharospasm. Early postoperative complication day after the operation, were edema (8 patients), hyperemia (5 patients) and haemorragia (1 patients) Other postoperative complications such as graft retraction, corneal dellen, necrosis of the graft, epithelial inclusion cysts, granuloma etc. we're not noticed. Conclusion: The excision of the pterygium with limbal autograft transplantation is highly efficient in terms of low recurrence rate.